FROM LOCAL FLAVOR TO GLOBAL APPEAL: LANGUAGE IN INDONESIAN BEAUTY BRANDING - Ramadhani, Innama; Sudarwati, Emy (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2025)
This study examined the language of Indonesian beauty branding, focusing on how language choices constructed brand identity and appealed to specific social groups. The research analyzed 79 data points, including brand names, slogans, taglines, and campaigns, which were collected from homepage banners and company profiles of seven beauty brand websites, using the Linguistic Landscape (LL) and Virtual Linguistic Landscape (VLL) frameworks. The sample included both local and international labels. A qualitative descriptive method with purposive sampling was applied, and the data were categorized by language form (monolingual or bilingual) and linguistic function (informative and symbolic). The findings showed a strong preference for English in conveying prestige, modernity, and global orientation. Bahasa Indonesia was employed to emphasize national pride and ensure accessibility, while occasional Arabic or Spanish terms targeted niche audiences. The dominance of symbolic over informative functions reflected strategic branding aimed at influencing consumer perceptions and appealing to defined social groups. This research contributed to the advancement of LL and VLL scholarships by extending their application to the under-explored domain of beauty branding in Indonesia. It demonstrated how multilingual branding operated simultaneously as a marketing tool and a vehicle for ideological expression, offering a framework for understanding how language choices in emerging markets reflected and reinforced socio-cultural values.